Steel magnolias - Harling, Robert, 1951-; Stark, Ray; Ross, Herbert, 1927-2001; Field, Sally; Parton, Dolly; Roberts, Julia, 1967-; Hannah, Daryl; Dukakis, Olympia; MacLaine, Shirley, 1934-; Skerritt, Tom; Shepard, Sam, 1943-2017; McDermott, Dylan; et al. (Culver City, Calif : Columbia TriStar Home Video, 2000)
"Six divas of the silver screen - Sally Field, Dolly Parton, Shirley MacLaine, Daryl Hannah, Olympia Dukakis and Julia Roberts - come together as bosom buddies in this hilarious and heartwarming story of life, love and loss in a small Louisiana Parish. At the center of the group is Shelby Eatenton (Roberts), newly married and joyfully pregnant, despite the fact that her diabetes could make childbirth life-threatening. Terrified and angry at the possibility of losing her only daughter, M'Lynn Eatenton (Field) looks to her four closest friends for strength and laughter as she battles her deepest fears of death in order to join Shelby in celebrating the miracle of new life"--Container
Originally produced as a motion picture in 1989
Special features: Director's commentary, deleted scenes, exclusive featurette, isolated music score, trailers, talent files, production notes
Scene selection list inserted in container
Director of photography, John A. Alonzo; editor, Paul Hirsch; music, George Delerue
Sally Field, Dolly Parton, Julia Roberts, Daryl Hannah, Olympia Dukakis, Shirley MacLaine, Tom Skerritt, Sam Shepard, Dylan McDermott, Kevin J. O'Connor
MPAA rating: PG ; Canadian Home Video rating: PG
Keywords: Harling, Robert, -- 1951- -- Film adaptations; Diabetics -- Drama; Mothers and daughters -- Drama; Friendship -- Drama; Feature films; Film adaptations; Fiction films; Video recordings for the hearing impaired